Palliative resection of primary site in advanced gastroenteropancreatic neuroendocrine tumors improves survivals - Kıvrak Salim, Derya; Bayram, Selami; Gömceli, İsmail; Çekin, Ayhan Hilmi; Karaca, Mustafa; Koçer, Murat; Yıldız, Mustafa (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Gastroenteropancreatic neuroendocrine tumors are rarely seen and have heterogeneous clinical outcomes. Mostly half of the patients had metastatic disease at presentation. Palliative resection of primary site in metastatic disease is still controversial.The aim of this study was to find out the influence of resection of primary tumor site on progression-free survival and overall survival in metastatic non-functioning gastroenteropancreatic neuroendocrine tumors. The secondary end point is to determine the prognostic factors influencing the survivals.Materials and Methods: This study was conducted at a single medical oncology center, Antalya Education and Research Hospital. Patients who had non-functioning metastatic gastroenteropancreatic neuroendocrine tumors with primary site resected or unresected were compared retrospectively. Resection of metastases was excluded.Results: Fifty-three patients were included in the study and 29 patients had primary tumor resection. The primary site resected group had favorable outcomes with the overall survival (median unreached) compared to the median overall survival of 30 months in the unresected group (p=0.001). Median progression-free survival was also better in the primary site resected group than the unresected group (60 months vs. 14 months, respectively) (p=0.013). In multivariate analysis, unresected primary site and high-grade tumors were found to be independent prognostic factors on low survivals (Hazard ratio (HR): 4.6; 95% CI: 1.21-17.47 and HR: 10.1; 95% CI: 1.15-88.84, respectively). Age (p=0.131), gender (p=0.051), chromogranin A level (p=0.104), Ki-67 index (p=0.550), tumor size (p=0.623), and primary tumor area (p=0.154) did not influence the overall survival.Conclusion: Gastroenteropancreatic neuroendocrine tumors with primary site resected had improved survivals when compared to the unresected group.